2020
DOI: 10.1038/s41589-020-0604-z
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery reveals a gut-restricted TGR5 agonist with anti-diabetic effects

Abstract: Bariatric surgery, the most effective treatment for obesity and type 2 diabetes, is associated with increased levels of the incretin hormone GLP-1 and changes in levels of circulating bile acids. The levels of individual bile acids in the GI tract following surgery, however, have remained largely unstudied. Using UPLC-MS-based quantification, we observed an increase in an endogenous bile acid, cholic acid-7-sulfate (CA7S), in the GI tract of both mice and humans after sleeve gastrectomy. We show that CA7S is a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(102 citation statements)
references
References 47 publications
5
79
1
Order By: Relevance
“…Because mice post-SG displayed higher levels of LCA in the portal vein, we hypothesized that more LCA was being synthesized by bacteria in the intestine of mice post-SG. Contrary to our hypothesis, we had observed a significant decrease in levels of LCA in the cecum of mice post-SG, while the levels of DCA and total BAs were unchanged (Chaudhari et al, 2020). We observed similar changes in stool samples from human patients that had undergone SG.…”
Section: Lca-triggered Ca7s Synthesis Induces Glp-1 Secretion In Entecontrasting
confidence: 99%
See 3 more Smart Citations
“…Because mice post-SG displayed higher levels of LCA in the portal vein, we hypothesized that more LCA was being synthesized by bacteria in the intestine of mice post-SG. Contrary to our hypothesis, we had observed a significant decrease in levels of LCA in the cecum of mice post-SG, while the levels of DCA and total BAs were unchanged (Chaudhari et al, 2020). We observed similar changes in stool samples from human patients that had undergone SG.…”
Section: Lca-triggered Ca7s Synthesis Induces Glp-1 Secretion In Entecontrasting
confidence: 99%
“…GLP-1 is a major mediator of diabetes remission post-SG (Kaska et al, 2016;Larraufie et al, 2019). Consistent with our previous studies, we observed an increase in circulating levels of GLP-1 in DIO mice that were subjected to SG (Chaudhari et al, 2020) (Figure 1F). However, treatment of DIO mice with antibiotics pre-and post-SG ablated the SG-mediated increase in GLP-1 secretion ( Figure 1G).…”
Section: Production Of Ca7s and Induction Of Glp-1 Requires A Microbiomesupporting
confidence: 92%
See 2 more Smart Citations
“…This is also supported by the finding that the jejunal contents of RYGB-operated rats stabilized barrier function in Caco-2 cells independently of FXR, since bile flow is redirected away from the upper/mid jejunum post-operatively. Nevertheless, future bile acid measurements of the duodenal and colonic contents of RYGB-operated rats by nuclear magnetic resonance spectroscopy are needed to identify the precise molecular mechanisms responsible for their barrier-stabilizing effects, akin to that performed for mouse cecal contents in the context of enhanced enteroendocrine cell function following VSG ( Chaudhari et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%